Decay-accelerating factor is not the only receptor for enterovirus 70. - Haddad, Alain. (University of Ottawa (Canada), 2002)
Enterovirus 70 (EV70) belongs to the family Picomaviridae and is a human pathogen responsible for acute hemorrhagic conjunctivitis. Unlike most human enteroviruses, the host range of EV70 encompasses a wide variety of non-primate mammalian cells in vitro. We demonstrated previously that EV70 uses decay-accelerating factor (DAF/CD55), a 70 kDa glycosyl-phospatidylinositol (GPI)-anchored protein, as a receptor on HeLa cells. Others have shown that DAF also facilitates the attachment of other human enteroviruses, including a number of coxsackieviruses and echoviruses; however, for some of these viruses additional surface proteins are essential for virus entry and infection, such as intercellular adhesion molecule 1 (ICAM-1) for coxsackievirus A21, and the coxsackie-adenovirus receptor (CAR) for coxsackie B viruses. One objective of the research described in this thesis was to determine if human DAF also functioned as a receptor for EV70 on other human cell lines. Another objective was to determine whether ICAM-1 or human CAR function as receptors for EV70. A third objective was to elucidate the potential role of non-primate DAF homologues in EV70 binding and infection. (Abstract shortened by UMI.)
Keywords: Biology, Cell.